2016
DOI: 10.1159/000446284
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Changes in Sleep, qEEG, Physiology, Behaviour and Neurochemistry in Rats Exposed to Repeated Social Defeat Stress

Abstract: Depression is a heterogeneous disorder characterized by alterations at psychological, behavioural, physiological, neurophysiological, and neurochemical levels. Social stress is a prevalent stress in man, and the repeated social defeat stress model in rats has been proposed as being the rodent equivalent to loss of control, which in subordinate animals produces alterations that resemble several of the cardinal symptoms found in depressed patients. Here, rats followed a resident-intruder protocol for 4 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…In an earlier paper we reported that SDL results in altered diurnal activity patterns and increased body temperature in the early morning (Bartlang et al 2015). In line with this, it was recently shown in rats that mild chronic subordination leads to reduced activity, altered sleeping patterns and increased body temperature, which suggests an increased metabolic rate as response to SDL (Ahnaou & Drinkenburg 2016), which is also reported in squirrels (Johren et al 1991, Kramer et al 1999. In line with Gorka and Adamik (1993), SDD did not influence bodyweight, but was accompanied by a reduction in food intake, pointing to an anabolic effect of stress during the active phase that is compensated by a reduction in energy intake.…”
Section: Timed Stressor Application Differently Affects Energy Metabosupporting
confidence: 73%
“…In an earlier paper we reported that SDL results in altered diurnal activity patterns and increased body temperature in the early morning (Bartlang et al 2015). In line with this, it was recently shown in rats that mild chronic subordination leads to reduced activity, altered sleeping patterns and increased body temperature, which suggests an increased metabolic rate as response to SDL (Ahnaou & Drinkenburg 2016), which is also reported in squirrels (Johren et al 1991, Kramer et al 1999. In line with Gorka and Adamik (1993), SDD did not influence bodyweight, but was accompanied by a reduction in food intake, pointing to an anabolic effect of stress during the active phase that is compensated by a reduction in energy intake.…”
Section: Timed Stressor Application Differently Affects Energy Metabosupporting
confidence: 73%
“…More recently, 4 days of social defeat stress were consistently shown to increase 5-HT levels in the hippocampus (Ahnaou and Drinkenburg, 2016). The inconsistency of 5-HT levels observed following social defeat stress may be due to observed different duration of social defeat stress.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, psychosocial stressors are among the major sources of stress. In rodents, social stress—in particular, a conflict with an aggressive mouse—has been shown to disrupt sleep ( 18 26 ). These alterations in the sleep architecture caused by social stress may result from interactions between stress and sleep regulatory circuits.…”
mentioning
confidence: 99%